Pemanfaatan Data Pola Penyakit Untuk Penguatan Perencanaan Dan Manajemen Pelayanan Rawat Jalan Di Puskesmas Darussalam Tahun 2025 - Murni Noviani Nasution; Balqis Nurmauli Damanik; Solihin; Annisa Febriana Siregar; Linawati Togatorop; Vinna Pratiwi Agustyn; Tifani Hadi Tri Wahyuni; Melinda Daya; Dhea Amanda Putri (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Outpatient services at community health centers experience a high and dynamic service burden influenced by evolving disease patterns in the community. However, the use of disease pattern data to support outpatient service management remains limited and is often restricted to administrative reporting purposes. This community service activity aimed to enhance the capacity of health workers and managers at Darussalam Community Health Center to utilize disease pattern data as a basis for managing outpatient service burden. A community-based participatory approach was applied through mentoring, training, and hands-on practice in data analysis using routine data from the Integrated Recording and Reporting System of Community Health Centers (SP2TP). The subjects of the activity were health workers and managerial staff at Darussalam Community Health Center. The results demonstrated an improvement in participants’ understanding and ability to analyze disease pattern data, reflected by an increase in average knowledge scores from a moderate to a high category. Behavioral changes were also observed, including increased data-based discussions, the emergence of internal change agents (local leaders), and the development of collective awareness regarding the importance of data-driven outpatient service management. This community service activity contributed to strengthening outpatient service management and fostering a data-driven work culture at Darussalam Community Health Center.